TSG-6 Secreted by Human Adipose Tissue-derived Mesenchymal Stem Cells Ameliorates DSS-induced colitis by Inducing M2 Macrophage Polarization in Mice - Woo-Jin Song (Nature Portfolio, 2017)
Abstract Previous studies have revealed that mesenchymal stem cells (MSCs) alleviate inflammatory bowel disease (IBD) by modulating inflammatory cytokines in the inflamed intestine. However, the mechanisms underlying these effects are not completely understood. We sought to investigate the therapeutic effects of human adipose tissue-derived (hAT)-MSCs in an IBD mouse model and to explore the mechanisms of the regulation of inflammation. Dextran sulfate sodium-induced colitis mice were infused with hAT-MSCs intraperitoneally and colon tissues were collected on day 10. hAT-MSCs were shown to induce the expression of M2 macrophage markers and to regulate the expression of pro- and anti-inflammatory cytokines in the colon. Quantitative real time-PCR analyses demonstrated that less than 20 hAT-MSCs, 0.001% of all intraperitoneally injected hAT-MSCs, were detected in the inflamed colon. To investigate the effects of hAT-MSC-secreted factors in vitro, transwell co-culture system was used, demonstrating that tumour necrosis factor-α-induced gene/protein 6 (TSG-6) released by hAT-MSCs induces M2 macrophages. In vivo, hAT-MSCs transfected with TSG-6 small interfering RNA, administered intraperitoneally, were not able to induce M2 macrophage phenotype switch in the inflamed colon and had no significant effects on IBD severity. In conclusion, hAT-MSC-produced TSG-6 can ameliorate IBD by inducing M2 macrophage switch in mice.